Eutectic melt crystallization of L10-FePt. Issue 5 (19th December 2018) - Zhang, Jingming; Li, Changning; Armstrong, Jason; Ren, Shenqiang
Abstract : Herein, we report the eutectic growth control of ordered L10 -FePt, which directs the nucleation, growth and crystallization of FePt sheets in a single-step reaction. Abstract : Herein, we report the eutectic growth control of ordered L10 -FePt, which directs the nucleation, growth and crystallization of FePt sheets in a single-step reaction. The nature of eutectic crystallization at the eutectic point suggests its role as a high-temperature solvent, exhibiting an advantage in the scale-up production of metastable alloys.